Iridoids and sesquiterpenoids from Valeriana officinalis and their bioactivities. (January 2023) - Shi, Dao-Qun; Liu, Jia-Jin; Feng, Yu-Mei; Zhou, Yan; Liao, Cai-Cen; Liu, Dan; Li, Rong-Tao; Li, Hong-Mei
Abstract: Twenty-six iridoids, including six undescribed ones (iridoidvols A−F) and an undescribed natural one, along with ten known sesquiterpenoids were isolated from the roots and rhizomes of Valeriana officinalis . Structurally, iridoidvol A is the first example of iridoid with sesquiterpenoid acid ester. In addition, all of the isolates were evaluated for anti-inflammatory and anti-influenza virus activities. Among them, isovaltrate isovaleroyloxyhydrin exhibited a significant inhibitory effect on NO production with an IC50 value of 19.00 μM. Graphical abstract: Image 1 Highlights: Six undescribed iridoids were isolated from Valeriana officinalis . Iridoidvol A was the first example of iridoid with sesquiterpenoid acid ester. Isovaltrate isovaleroyloxyhydrin showed obvious anti-inflammatory activity.